IMPLEMENTASI KURIKULUM MERDEKA DALAM SEKOLAH PENGGERAK - Febia Ghina Tsuraya; Nurul Azzahra; Salsabila Azahra; Sekar Puan Maharani (Pusat Riset dan Inovasi Nasional, 2022)
The occurrence of the covid-19 pandemic caused a forced change in learning methods. The changes that occur are changes from the 2013 curriculum to an independent curriculum whose goal is to catch up on learning. This study aims to identify and examine the